Safety and efficacy of dronedarone from clinical trials to real-world evidence: implications for its use in atrial fibrillation. Issue 12 (19th July 2019) - Boriani, Giuseppe; Blomström-Lundqvist, Carina; Hohnloser, Stefan H; Bergfeldt, Lennart; Botto, Giovanni L; Capucci, Alessandro; Lozano, Ignacio Fernández; Goette, Andreas; Israel, Carsten W; Merino, José L; Camm, A John
Abstract: Efficacy and safety of dronedarone was shown in the ATHENA trial for paroxysmal or persistent atrial fibrillation (AF) patients. Further trials revealed safety concerns in patients with heart failure and permanent AF. This review summarizes insights from recent real-world studies and meta-analyses, including reports on efficacy, with focus on liver safety, mortality risk in patients with paroxysmal/persistent AF, and interactions of dronedarone with direct oral anticoagulants. Reports of rapidly progressing liver failure in dronedarone-prescribed patients in 2011 led to regulatory cautions about potential liver toxicity. Recent real-world evidence suggests dronedarone liver safety profile is similar to other antiarrhythmics and liver toxicity could be equally common with many Class III antiarrhythmics. Dronedarone safety concerns (increased mortality in patients with permanent AF) were raised based on randomized controlled trials (RCT) (ANDROMEDA and PALLAS), but comedication with digoxin may have increased the mortality rates in PALLAS, considering the dronedarone–digoxin pharmacokinetic (PK) interaction. Real-world data on apixaban–dronedarone interactions and edoxaban RCT observations suggest no significant safety risks for these drug combinations. Median trough plasma concentrations of dabigatran 110 mg during concomitant use with dronedarone are at acceptable levels, while PK data on the rivaroxaban–dronedarone interaction are unavailable. In RCTs and real-world studies, dronedarone significantly reduces AF burden and cardiovascular hospitalizations, and demonstrates a low risk for proarrhythmia in patients with paroxysmal or persistent AF. The concerns on liver safety must be balanced against the significant reduction in hospitalizations in patients with non-permanent AF and low risk for proarrhythmias following dronedarone treatment.